1980
DOI: 10.1136/bmj.280.6218.899
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae type B meningitis: a contagious disease of children.

Abstract: Summary and conclusionsThe families of 126 consecutive patients with Haemophilus influenzae type B meningitis were surveyed for secondary invasive H influenzae disease among household contacts. A total of 120 of the families were contacted. In six cases no contact was possible and the medical record was reviewed. Some 555 household contacts were found; 31% (171) were under 5 years of age. A secondary case was defined as a household contact with H influenzae type B isolated from blood or cerebrospinal fluid mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…A history of case contact occurred only in the meningococcal group and the culture-negative group which, together with the greater fluctuation in annual incidence in the meningococcal group, is consistent with the reputation of the meningococcus for case to case spread. No secondary cases and no significant annual fluctuation was observed in the haemophilus group, although recent reports from America have documented case to case spread (Ward et al 1979;Glode et al 1980). It is, at present, our opinion that these sporadic secondary cases of haemophilus meningitis are insufficient justification for giving chemoprophylaxis to contacts of this disease (Davey & Cruickshank, 1979;Davey, Cruickshank & Geddes, 1980).…”
Section: Outcome -Pneumococcal Groupmentioning
confidence: 85%
“…A history of case contact occurred only in the meningococcal group and the culture-negative group which, together with the greater fluctuation in annual incidence in the meningococcal group, is consistent with the reputation of the meningococcus for case to case spread. No secondary cases and no significant annual fluctuation was observed in the haemophilus group, although recent reports from America have documented case to case spread (Ward et al 1979;Glode et al 1980). It is, at present, our opinion that these sporadic secondary cases of haemophilus meningitis are insufficient justification for giving chemoprophylaxis to contacts of this disease (Davey & Cruickshank, 1979;Davey, Cruickshank & Geddes, 1980).…”
Section: Outcome -Pneumococcal Groupmentioning
confidence: 85%
“…It took a nation-wide survey in the USA (Ward et al, 1979) to establish that the likelihood of a case of haemophilus meningitis occurring in a household within 30 days of the occurrence of an index case was much higher (the authors' calculation was 585 times higher) than in the general population. Secondary spread in day-care centres was already well documented (for references see Ward et al, 1979), and the new attitude to the epidemiology of haemophilus meningitis was embodied by Glode et al (1980) in the title of their paper, in which they described it as "a contagious disease of children". OMP typing has confirmed that secondary cases of this kind are caused by the strains causing their respective index cases (Loeb and Smith, 1980;Barton, Granoff and Barenkamp, 1983;, and there is therefore no need to postulate any other factor to explain these case-associations.…”
Section: Capsular Type Bmentioning
confidence: 99%
“…Although uncommon, secondary cases of disease due to Haemophilus inJEuenzae of capsular type b are well documented, and can occur within a patient's family or among close non-family contacts (Glode et al, 1980). Their secondary nature is recognisable because of the micro-organism's possession of the type b capsule.…”
Section: Introductionmentioning
confidence: 99%